London Belles - Groves, Annie (United Kingdom HarperCollins Publishers, 2011)
A companion to "Business Policy" by the same authors, this book provides an extensive set of topical and up-to-date cases in business policy and corporate strategy. The topics include: business framework policy; strategic analysis and direction; business growth and decline; strategy implementation.
Keywords: Manners and Customs -- England--London